“Giving back the gaze”: exploring complex and multifarious self-representations in the work of Myra Greene and Renée Cox - Jones-Berney, Jessica K. (2010)
In this thesis I explore photographic attempts by African American women artists to produce experimental and diverse self-representations of the black female body. It considers the works of two black women photographers, Myra Greene and Renée Cox, and their contribution to a new visual language that focuses on abstractions and multifarious depictions of the black female body to explore the ever shifting identity of African Americans.